2019
DOI: 10.1177/2333794x19860659
|View full text |Cite
|
Sign up to set email alerts
|

Reintegration Into School After Treatment for a Brain Tumor: The Child’s Perspective

Abstract: This multiple case study investigated perspectives of childhood brain tumor survivors on reintegration into school over a 2-year period. Semistructured interviews were conducted with 5 children at 3 times to obtain an extensive view of their overall school experience. Thematic analysis of data resulted in 4 themes: “school life and participation,” “peer relations and friendships,” “performance and difficulties,” and “support and follow-up.” Childhood brain tumor survivors consider school attendance as part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 46 publications
0
26
0
2
Order By: Relevance
“…56 Special treatment-even when very much needed, such as assistance with schoolwork and class participation-often made them feel abnormal when delivered in front of peers. 29,51,53 Some children and adolescents-predominantly survivorsreported downplaying their problems and trying not to attract attention from classmates and school staff to appear more like their friends and peers. 18,29 They also found it frustrating and upsetting to not be able to do activities they considered normal, such as driving and playing sport.…”
Section: A Constant Cloud Of Uncertaintymentioning
confidence: 99%
“…56 Special treatment-even when very much needed, such as assistance with schoolwork and class participation-often made them feel abnormal when delivered in front of peers. 29,51,53 Some children and adolescents-predominantly survivorsreported downplaying their problems and trying not to attract attention from classmates and school staff to appear more like their friends and peers. 18,29 They also found it frustrating and upsetting to not be able to do activities they considered normal, such as driving and playing sport.…”
Section: A Constant Cloud Of Uncertaintymentioning
confidence: 99%
“…I don't think you will improve if you don't do anything about it. (Stephanie Vanclooster et al, 2019) Importance of encouragement Conversely, not improving despite working hard was disheartening for children and adolescents (Cheung et al, 2019;Vance et al, 2004;Vanclooster et al, 2019b;Vanclooster, Bilsen, et al, 2019): I feel a significant decline in my learning capability, I always get poor results from the tests and examinations, which make me feel very disappointed and distressed (Cheung et al, 2019). In Boydell et al (2008), adolescents identified a need for extra encouragement and recognition of their work: I think I could have used more of that (encouragement).…”
Section: Successes and Failuresmentioning
confidence: 99%
“…And that was really hard. (Bruce et al, 2008) Parents and diagnosed children often pre-empted bullying and worried about it worsening in the future (Vance et al, 2004;Vanclooster, Bilsen, et al, 2019;Zwiers, Campbell, Evans, & Kirkwood, 2015):…”
Section: Devastation Of Bullyingmentioning
confidence: 99%
See 1 more Smart Citation
“…Children’s own experiences appear to have received insufficient investigation given the extensive concerns related to educational attainment. Retrospective reporting [ 20 ] and small sample sizes [ 21 ] are further issues that challenge the drawing together of robust recommendations from individual studies. Children’s own perceptions seem to have a strong focus on the social aspects of school life [ 22 ]; these can form both the positive aspects of school and some of the more challenging aspects as reported by children and adolescents themselves [ 23 ].…”
Section: Introductionmentioning
confidence: 99%